A High-Efficiency Secure Communication Scheme in Vehicle Ad-hoc Networks - Zhao, Shushan (Indian Journal of Computer Science, 2025)
Vehicle Ad-hoc Networks (VANETs) have come into being with development of many technologies, but security and privacy is a big concern to address before they can be applied. In this work, we study existing requirements and cryptographic solutions on security and privacy protection in vehicle networks, identify their weaknesses and limitations, and propose an improved security scheme to address the weaknesses and limitations. The proposed solution is analyzed and evaluated theoretically and with simulation, to demonstrate its security features and high efficiency.